Low-temperature-resistant early-strength alkali-free liquid accelerator and preparation method thereof
By adding specific components to the alkali-free liquid accelerator, such as aluminum sulfate, β-cyclodextrin-embedded sodium thiocyanate, etc., the problem of insufficient anti-freezing properties of alkali-free accelerator in the prior art in the low temperature environment is solved, and the rapid condensation and high strength of concrete at low temperatures is achieved.
Patent Information
- Application Number
- CN202510315125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing sulfate alkali-free quick-coagulant has insufficient anti-freeze performance under low temperature environments, resulting in an extended settling time of concrete and an increase in viscosity, which affects construction safety and strength.
A low-temperature and early-strength-resistant alkali-free liquid fast-setting agent is used, including aluminum sulfate, β-cyclodextrin-embedded sodium thiocyanate, calcium hydroxide inactivator, fiber, hydrophilic polymer substance, cationic surfactant and polymer aluminum chloride. Through the synergistic effect of these components, the anti-freeze properties of concrete are improved.
This liquid accelerator can significantly shorten the settling time of concrete under low temperature environments, reduce the viscosity of cement mortar, improve the later strength and frost resistance of concrete, and ensure the safety and quality of construction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkali-free liquid accelerating setting agent, in particular to a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent and a preparation method thereof. Background Art
[0002] In recent years, shotcrete has been widely used and recognized in various engineering fields, including the construction of tunnels, underground urban spaces, mines and foundation pit support. Shotcrete is widely used in tunnel construction in my country because of its convenient and fast construction technology and can reduce the required manpower. If the stability of shotcrete is not enough, it will cause the surrounding rock to become unstable, posing a serious threat to the safety of tunnel construction. Accelerator is an indispensable and important component in shotcrete mortar.
[0003] Sulfate alkali-free accelerator is a type of accelerator. Sulfate alkali-free accelerator cannot meet the setting time requirements of cement slurry, resulting in large rebound of shotcrete. In order to solve this problem, a liquid accelerator with fluoroaluminate is called fluorine-containing alkali-free liquid accelerator (AF-hf). Fluoroaluminate is often mixed with aluminum sulfate to improve the coagulation of alkali-free liquid accelerator. It is worth noting that fluoroaluminate is a liquid mixture produced by dissolving aluminum hydroxide and excess hydrofluoric acid. Although the addition of fluoroaluminate shortens the setting time, the fluorine-containing alkali-free liquid accelerator increases the Al 3+ While increasing the content of fluoride to extend the age of cement paste, it also introduces a large amount of fluoride ions.
[0004] Fluorine-containing alkali-free liquid accelerators inhibit the hydration of C(3)S, increase the number of harmful pores, reduce the pH value, and reduce the binding capacity of shotcrete for chloride ions. Corrosion product detection shows that shotcrete containing fluorine-containing alkali-free liquid accelerators is prone to the rapid formation of loose corrosion products, mainly Fe2O3, which accelerates the corrosion rate of steel bars. The presence of fluorine may affect the compatibility of cement with admixtures (such as fly ash and slag powder), thereby affecting the performance of concrete. Aluminum sulfate-based alkali-free liquid accelerators mainly provide early strength and shorten the setting time by hydrating to form hydration products such as calcium aluminate (AFt) and hydrated calcium silicate (CSH) gel; while fluoroaluminate-based alkali-free liquid accelerators provide early strength and shorten the setting time by consuming gypsum and generating hydration products such as hydrated calcium aluminate (CAH) gel and calcium hydroxide (CH). When the content of fluorosilicic slag is high, fluoride ions react with calcium hydroxide to generate excessive calcium fluoride (CaF2) precipitation, which may have a coating effect on cement particles and delay cement hydration. This coating effect reduces the contact area between cement particles and water, thereby slowing down the rate of hydration reaction. Although calcium fluoride precipitation may delay the later hydration of C3S, fluoroaluminate-based alkali-free liquid accelerators can improve the strength of concrete in the early stages by promoting the hydration of C3A and the formation of AFt. And when C3S begins to hydrate, it will gradually increase the concentration of the colloidal solution. The increase in the concentration of the colloidal solution will lead to an increase in the viscosity of the cement paste and slow down the rate of cement hydration reaction, because the mutual collision and aggregation between colloidal particles reduce the chance of reaction with water, which helps to delay the setting time of cement.
[0005] Fluoroaluminate (AAF)-based alkali-free liquid accelerators show faster solidification effect at low ambient temperature and better adaptability to low ambient temperature. However, the performance of aluminum sulfate-based alkali-free liquid accelerators under low temperature conditions may not be as good as that of fluoroaluminate-based accelerators. Low ambient temperature promotes the hydrolysis of aluminum ions into aluminum hydroxide gel precipitation, reduces the dissolution stability of aluminum sulfate inorganic salts, and makes it easy to freeze and fail in low temperature environment. The difference in antifreeze performance between calcium aluminate hydrate (CAH) gel and calcium silicate hydrate (CSH) gel is as follows. Studies have shown that even in the absence of pore water, ultra-low temperature corrosion can destroy the CSH structure, while the doping of aluminum atoms can effectively stabilize the structure of CSH. Specifically, under ultra-low temperature corrosion, the silicon-oxygen chain of aluminum-free CSH breaks, producing more defect vacancies, resulting in a decrease in its d002 interlayer space, the collapse of the basic component volume, and further formation of microcracks. In contrast, the aluminum-silicon-oxygen chain of CASH is more stable, with a longer average chain length, and even slight polymerization occurs. Unlike CSH basic colloid units, CASH basic colloid units will not easily collapse under ultra-low temperature erosion (Zhu X, Ren Q, He B, et al. Upscaling degradation of cementitious calcium (aluminate) silicate hydrate upon ultra-low temperature attack: A multiscale insight and a bottom-up enhancement route [J]. Composites Part B: Engineering, 2022, 243: 110122.). Therefore, the present invention proposes a low-temperature resistant early-strength alkali-free liquid accelerator and a preparation method thereof. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, one of the objects of the present invention is to provide a low-temperature resistant and early-strength alkali-free liquid accelerator, which can improve the antifreeze performance of sulfate alkali-free accelerator, reduce the viscosity of cement mortar, promote the hydration reaction of C3S, shorten the setting time of concrete, and improve the later strength of concrete.
[0007] The second object of the present invention is to provide a method for preparing a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent, which is simple to prepare and convenient for on-site construction.
[0008] The third object of the present invention is to provide a concrete, in which the above-mentioned low-temperature resistant and early-strengthening alkali-free liquid accelerating agent is used during the concrete construction process.
[0009] One of the purposes of the present invention is achieved by the following technical solution: A low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent comprises 12 to 15 parts of aluminum sulfate, 2 to 5 parts of sodium thiocyanate embedded in beta-cyclodextrin, 5 to 8 parts of calcium hydroxide deactivator, 3 to 5 parts of fiber, 5 to 10 parts of hydrophilic polymer, 3 to 5 parts of cationic surfactant, 6 to 10 parts of polyaluminum chloride and 2 to 3 parts of air entraining agent.
[0010] Furthermore, it includes 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in beta-cyclodextrin, 8 parts of calcium hydroxide deactivator, 3 parts of fiber, 5 parts of hydrophilic polymer substance, 3 parts of cationic surfactant, 10 parts of polyaluminum chloride, and 2 parts of air entraining agent.
[0011] Furthermore, the calcium hydroxide deactivator is one or both of a carboxylate corrosion inhibitor and silica fume.
[0012] Furthermore, the hydrophilic polymer substance is one or both of polyethylene oxide (PEO) and polyacrylamide (PAM).
[0013] Furthermore, the cationic surfactant is one or both of dodecyl dimethyl amine oxide and dodecylamine polyoxyethylene ether.
[0014] Furthermore, the fiber is one or more of fiber steel fiber, glass fiber, basalt fiber, polypropylene fiber, nano carbon fiber, and polyacrylonitrile fiber.
[0015] Furthermore, the air entraining agent is one or more of coconut oil fatty acid diethanolamide, sodium rosin acid, and triterpenoid saponin.
[0016] Furthermore, the preparation method of the β-cyclodextrin-embedded sodium thiocyanate comprises the following steps: S1. Weigh β-cyclodextrin, add it into 70°C distilled water, stir and dissolve it, and adjust the pH to 7.4 to obtain a β-cyclodextrin solution; S2. Weigh sodium thiocyanate and prepare a sodium thiocyanate ethanol solution in a mass ratio of 1:1. Slowly add the sodium thiocyanate ethanol solution into the β-cyclodextrin solution and stir at a constant temperature of 60° C. to 65° C. to promote the sodium thiocyanate molecules to enter the hydrophobic cavity of the β-cyclodextrin to form an inclusion complex. Filter and dry to obtain the sodium thiocyanate embedded in the β-cyclodextrin.
[0017] The second object of the present invention is achieved by adopting the following technical solution: A method for preparing a low-temperature resistant early-strength alkali-free liquid accelerating setting agent comprises the following steps: S1. Weigh the raw materials of each component of the low-temperature resistant and early-strength alkali-free liquid accelerating setting agent according to the formula amount; S2, heating the deionized water to 70-85°C, then adding the aluminum sulfate, stirring until completely dissolved; cooling the solution to below 55°C, then adding the β-cyclodextrin-encapsulated sodium thiocyanate, the calcium hydroxide deactivator, the fiber, the hydrophilic polymer, the cationic surfactant, and the polyaluminum chloride, and stirring evenly; S3, adding the air entraining agent to the solution of step S2, stirring evenly, and cooling to room temperature to obtain the low-temperature stable and early-strengthening alkali-free liquid accelerating agent.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a low-temperature resistant and early-strengthening alkali-free liquid accelerating agent. Sodium thiocyanate (NaSCN) can reduce the freezing point of water in concrete, so that cement can be normally hydrated at low temperatures. Sodium thiocyanate is embedded with beta-cyclodextrin to avoid salting out of sodium thiocyanate due to low solubility at low temperatures. A calcium hydroxide deactivator can react with calcium hydroxide, which is helpful to refine the pore structure of concrete, increase the gel amount and gel porosity, but reduce the capillary porosity, enhance the compactness of concrete, thereby reducing the transportation of water in concrete, improving the durability of concrete, and thus improving the antifreeze performance of concrete. Fibers can form a random structure in concrete, enhance the restraint force inside concrete, offset a part of expansion stress, reduce deformation, and inhibit further expansion of cracks, thereby improving the antifreeze performance of concrete. The hydrophilic long side chain in the molecular structure of the hydrophilic polymer substance can adsorb and fix free water molecules, increase the viscosity of mixing water, and this water retention effect can reduce the free water in cement paste, thereby reducing the fluidity and viscosity of free water. Cationic surfactants carry positive charges. When they are adsorbed onto the surface of cement particles, they can neutralize the negative charges on the surface of cement particles and reduce the repulsive force between cement particles. Therefore, they can be used as flocculants to promote the flocculation of cement particles in cement paste, thereby reducing the number of free cement particles in cement paste. Part of the free water is also bound inside the floccules, reducing the free water content. At the same time, the internal friction of the cement paste is reduced, maintaining the dispersed state of cement particles, thereby reducing the viscosity of the cement paste. After the viscosity is reduced, the fluidity of the cement paste is improved. It can be seen that hydrophilic polymers and cationic surfactants The agent can synergistically reduce the flow of free water in the cement paste, promote the later hydration reaction of C3S, reduce the setting time of the cement paste, and improve the later setting strength of concrete. It effectively solves the problem that as the hydration of C3S proceeds, the amount of hydrated calcium silicate gel generated gradually increases, and these gel particles form a colloidal solution in the solution. The concentration of the colloidal solution itself increases, thereby delaying the setting time of cement; polyaluminium chloride can achieve the doping of aluminium atoms in the hydrated calcium silicate (CSH) gel to form CASH. The antifreeze performance of CASH gel is good, thereby improving the antifreeze performance of the sulfate alkali-free quick-setting agent. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0020] Sodium bentonite was purchased from Hubei Kewode Chemical Co., Ltd.; Gypsum (CaSO4·2H2O) was purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0021] Example 1 The present embodiment provides a low-temperature resistant and early-strengthening alkali-free liquid accelerator, comprising 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in β-cyclodextrin, 8 parts of a calcium hydroxide deactivator carboxylate-type corrosion inhibitor, 3 parts of steel fiber, 5 parts of a hydrophilic polymer substance polyethylene oxide, 3 parts of a cationic surfactant dodecyl dimethyl amine oxide, 10 parts of polyaluminum chloride, and 2 parts of an air-entraining agent coconut oil fatty acid diethanolamide.
[0022] β-cyclodextrin-encapsulated sodium thiocyanate (NaSCN) can lower the freezing point of water in concrete, allowing cement to be normally hydrated at low temperatures. Sodium thiocyanate is coated with nanocarriers to avoid salting out of sodium thiocyanate due to its low solubility at low temperatures.
[0023] The preparation method of β-cyclodextrin-embedded sodium thiocyanate comprises the following steps: S1. Weigh β-cyclodextrin, add it into 70°C distilled water, stir and dissolve it, and adjust the pH to 7.4 to obtain a β-cyclodextrin solution; S2. Weigh sodium thiocyanate and prepare a sodium thiocyanate ethanol solution in a mass ratio of 1:1. Slowly add the sodium thiocyanate ethanol solution into the β-cyclodextrin solution and stir at a constant temperature of 60°C to 65°C to promote the sodium thiocyanate molecules to enter the hydrophobic cavity of β-cyclodextrin to form an inclusion complex. Filter and dry to obtain β-cyclodextrin-encapsulated sodium thiocyanate.
[0024] Silica fume is an ultrafine siliceous material that can improve the early strength of concrete, and the silica in the volcanic ash reacts with calcium hydroxide, a by-product of cement hydration, to produce more calcium silicate hydrate (CSH), which increases the gel volume and gel porosity but reduces capillary porosity, thereby reducing water transport in concrete, thereby improving durability and long-term strength.
[0025] Carboxylate corrosion inhibitors can react with calcium hydroxide (CH) in concrete to form calcium carboxylate, which helps reduce the content of calcium hydroxide in concrete, prevent calcium hydroxide from easily reacting with acidic substances in the environment, causing corrosion of concrete, and improve the durability of concrete. Carboxylate corrosion inhibitors also react with sulfate ions in gypsum to reduce the chance of sulfate reacting with tricalcium aluminate (C3A) to form ettringite, thereby reducing the content of ettringite, reducing the risk of concrete expansion, cracking and damage.
[0026] Fibers can form a random structure in concrete, enhance the internal restraint of concrete, offset part of the expansion stress, reduce deformation, inhibit further expansion of cracks, and thus improve the frost resistance of concrete.
[0027] The long hydrophilic side chains in the molecular structure of hydrophilic polymers can adsorb and fix free water molecules, increasing the viscosity of mixing water. This water retention effect can reduce the free water in the cement paste, thereby reducing the fluidity and viscosity of the free water.
[0028] Silane coupling agents such as KH570 are used to graft CSH on the surface to improve its dispersion in cement slurry and enhance its low-temperature early strength properties.
[0029] During the hydration process, cement particles react with water to generate hydration products, such as calcium silicate gel (CSH) and calcium hydroxide (Ca(OH)2), which are usually negatively charged. Cationic surfactants carry positive charges. When they are adsorbed onto the surface of cement particles, they can neutralize the negative charges on the surface of cement particles, reducing the repulsive force between cement particles. Therefore, they can be used as flocculants to promote the flocculation of cement particles in cement paste, thereby reducing the number of free cement particles in cement paste. Part of the free water is also bound inside the flocculent, reducing the free water content, while reducing the internal friction of the cement paste, maintaining the dispersed state of cement particles, thereby reducing the viscosity of the cement paste. After the viscosity is reduced, the fluidity of the cement paste is improved.
[0030] Example 2 The present embodiment provides a low-temperature resistant and early-strengthening alkali-free liquid accelerator, which comprises 12 parts of aluminum sulfate, 5 parts of sodium thiocyanate (NaSCN) embedded in beta-cyclodextrin, 5 parts of silica fume as a calcium hydroxide deactivator, 4 parts of glass fiber, 8 parts of polyacrylamide as a hydrophilic polymer, 5 parts of dodecylamine polyoxyethylene ether as a cationic surfactant, 8 parts of polyaluminum chloride, and 3 parts of sodium rosin acid as an air entraining agent.
[0031] Example 3 The present embodiment provides a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent, which comprises 13 parts of aluminum sulfate, 3 parts of sodium thiocyanate embedded in beta-cyclodextrin, 6 parts of silica fume as a calcium hydroxide deactivator, 5 parts of basalt fiber, 10 parts of polyacrylamide as a hydrophilic polymer, 4 parts of dodecyl dimethyl amine oxide as a cationic surfactant, 6 parts of polyaluminum chloride, and 3 parts of triterpenoid saponin as an air entraining agent.
[0032] Comparative Example 1 Different from Example 1, this comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerator, including 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate, 8 parts of calcium hydroxide deactivator carboxylate erosion inhibitor, 3 parts of steel fiber, 5 parts of hydrophilic polymer polyethylene oxide, 3 parts of cationic surfactant dodecyl dimethyl amine oxide, 10 parts of polyaluminum chloride, and 2 parts of coconut oil fatty acid diethanolamide, an air entraining agent.
[0033] Comparative Example 2 The present comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerator. The difference from Example 1 is that the present comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerator, comprising 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate, 8 parts of a calcium hydroxide deactivator carboxylate erosion inhibitor, 3 parts of steel fiber, 5 parts of a hydrophilic polymer substance polyethylene oxide, 3 parts of a cationic surfactant dodecyl dimethyl amine oxide, and 2 parts of an air entraining agent coconut oil fatty acid diethanolamide.
[0034] Comparative Example 3 The present comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent, comprising 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in beta-cyclodextrin, 3 parts of steel fiber, 5 parts of polyethylene oxide, a hydrophilic polymer, 3 parts of dodecyl dimethyl amine oxide, a cationic surfactant, 10 parts of polyaluminum chloride, and 2 parts of coconut oil fatty acid diethanolamide, an air entraining agent.
[0035] Comparative Example 4 The comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent, comprising 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in beta-cyclodextrin, 8 parts of carboxylate corrosion inhibitor as a calcium hydroxide deactivator, 3 parts of steel fiber, 3 parts of cationic surfactant dodecyl dimethyl amine oxide, 10 parts of polyaluminum chloride, and 2 parts of coconut oil fatty acid diethanolamide as an air entraining agent.
[0036] Comparative Example 5 The comparative example provides a low-temperature resistant and early-strengthening alkali-free liquid accelerating setting agent, comprising 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in beta-cyclodextrin, 8 parts of carboxylate corrosion inhibitor as a calcium hydroxide deactivator, 3 parts of steel fiber, 10 parts of polyaluminum chloride, and 2 parts of coconut oil fatty acid diethanolamide as an air entraining agent.
[0037] Experimental example Portland cement raw material synthesis Tricalcium silicate (C3S) was synthesized by compacting a mixture of reagent grade Ca(OH)2 and SiO2 (molar ratio of 3:1), calcining once at 1500 °C for 2 h, and then grinding, which was repeated 5 times for 10 h.
[0038] Tricalcium aluminate (C3A) was synthesized by compacting a mixture of reagent grade Ca(OH)2 and Al2O3 (molar ratio of 6:1), calcining at 1400℃ for 3h, and then grinding. This was repeated 5 times and calcined for 10h.
[0039] According to the mass percentage of the total mass, 75% of tricalcium silicate, 20% of tricalcium aluminate and 5% of gypsum were mixed evenly to form a silicate cement sample.
[0040] How to use low temperature resistant early strength alkali-free liquid accelerator Pure slurry with liquid accelerator: put sand, sodium bentonite, 400g silicate cement sample into a stirring pot, stir at low speed for 30s, add weighed low temperature early strength alkali-free liquid accelerator provided by Example 1-3 and Comparative Example 1-5 at once with a 50mL syringe, the mass ratio of low temperature early strength alkali-free liquid accelerator to silicate cement sample is 3.0%, stir at low speed for 5s, add weighed water (140g minus the amount of water in the low temperature early strength alkali-free liquid accelerator), stir at high speed for 15s, and immediately pour into a mold of 70mm×70mm×70mm at 20±2℃ after stirring, tamp with a knife, vibrate gently several times, scrape off excess pure slurry, and smooth the surface. The final setting time of cement slurry starts from the addition of water, and silicate cement mortar samples are obtained, which are recorded as Example 1-3 group and Comparative Example 1-5 group. The silicate cement mortar samples of Example 1-3 and Comparative Example 1-5 were repeated 9 times. All silicate cement mortars were placed in a moisture curing box at a temperature of -20±2°C and a relative humidity of 95% HR. The following experiments were carried out: the setting time experiment, the compressive strength test of the concrete specimens, and the antifreeze performance test were repeated 3 times respectively.
[0041] The strength of masonry mortar is expressed in strength grades. The mortar strength grade is determined by measuring the compressive strength value (in MPa) of a cubic specimen with a side length of 70.7 mm under standard curing conditions (temperature (20±2)℃, relative humidity above 90%) using standard test methods at 28 days.
[0042] Experimental Example 1: Coagulation Time The setting time of Examples 1-3 and Comparative Examples 1-5 was measured using a Vicat apparatus (Wuxi Jianyi Experimental Equipment Co., Ltd.). The test method for setting time of cement paste is carried out in accordance with the Chinese standard GB / T35159-2017 "Accelerator for Shotcrete". The initial setting time and final setting time of cement paste were measured using a Vicat apparatus. The Vicat apparatus is an instrument for measuring the setting time of cement. It consists of a test needle with a specific diameter and weight and a scale. The method of use is as follows: The steps for determining the initial setting time of cement slurry are as follows: The specimen (test mold with cement paste) is placed in a moisture curing box to maintain the humidity and temperature of the cement paste to simulate the actual curing conditions. The first setting time measurement is started 30 minutes after adding water. The test mold with cement paste is taken out of the moisture curing box and placed under the test needle of the Vicat instrument. The test needle of the Vicat instrument is lowered so that it touches the surface of the cement paste lightly. After the test needle touches the surface of the cement paste, the screw on the Vicat instrument needs to be tightened to fix the position of the test needle to ensure that the test needle does not move during the test. This process takes about 1 to 2 seconds. After tightening the screw, suddenly loosen the screw, which will allow the test needle to sink freely and vertically into the cement paste under the action of gravity. Observe the sinking of the test needle in the cement paste. The sinking depth of the test needle will vary depending on the setting state of the cement paste. If the cement paste has not yet initially set, the test needle will sink deeper; if it has already initially set, the depth of the test needle will be shallower. Observe the scale reading when the test needle stops sinking in the cement paste, which can reflect the setting state of the cement paste. After the test needle sinks, wait for 30 seconds, and then observe the test needle reading on the scale. This reading can reflect the setting state of the cement paste after a certain period of time.
[0043] When the test needle sinks to a certain depth (usually 1.3mm±0.5mm), the cement paste can be considered to have initially set. This process needs to be repeated several times until two consecutive test results are the same.
[0044] The steps for determining the final setting time of cement slurry are as follows: After the initial setting time is determined, the test mold containing cement slurry needs to be taken out from under the glass plate and flipped 180 degrees in a translational manner. This is done to prevent the cement slurry at the bottom of the test mold from hardening prematurely due to long-term contact with the glass plate, which will affect the determination of the final setting time. After flipping, the large end of the test mold is placed upward and the small end is placed downward on the glass plate. The flipped test mold needs to be placed in the moisture curing box again for continued curing at a temperature of -20±2℃ and a relative humidity of 95% HR to maintain the humidity and temperature of the cement slurry and simulate actual curing conditions. When approaching the final setting time, it is necessary to measure every 15 minutes. This is because final setting is a gradual process and frequent checks are required to determine the exact final setting time. When the test needle sinks into the specimen to a depth of 0.5mm, the cement is considered to have reached the final setting state. This standard means that the cement paste has completely lost its plasticity and has become hard enough so that the test needle cannot leave obvious marks on the surface. In order to ensure the accuracy of the test results, it is necessary to test at two other different points on the specimen. If the test results of these three points all show that the test needle has sunk to a depth of 0.5mm, then it can be determined that the cement paste has reached the final setting state. Only when the results of the three tests are consistent can it be finally determined that the cement paste has reached the final setting state. This is to ensure the reliability of the test results and avoid misjudgment due to uneven local hardening.
[0045] Through these steps, the final setting time of cement paste can be accurately determined, which is very important for construction and project quality control. The final setting time is an important sign of the transition of cement paste from plastic state to hard state, which is of guiding significance for determining the construction timing and subsequent construction steps.
[0046] The results of the coagulation time measurements of Example 1-3 and Comparative Example 1-5 are shown in Table 1.
[0047] Table 1
[0048] The setting time of cement can be divided into initial setting and final setting. The time required from the time water is added to the time when the cement slurry begins to lose plasticity and fluidity decreases is called the initial setting time. The time required from the time water is added to the time when the cement slurry completely loses plasticity and begins to have a certain structural strength is called the final setting time. The initial setting and final setting of cement are specified through tests. The setting time required by the Chinese standard GB / T35159-2017 "Accelerator for Shotcrete" is as follows: The initial setting time of alkali-free liquid accelerator should be within 5 minutes, and the final setting time should be within 12 minutes. The results in Table 1 show that the initial setting time and final setting time of Examples 1-3 are shorter than those of Comparative Examples 1-5. Compared with Comparative Example 1, the initial setting time and final setting time of Examples 1-3 are equivalent to those of Comparative Example 1, and no salting out of sodium thiocyanate is found, indicating that sodium thiocyanate is coated with nanocarriers to avoid being affected by its low solubility at low temperatures. Compared with Comparative Example 2, the initial setting time and final setting time of Examples 1-3 are significantly shorter than those of Comparative Example 2, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH. The antifreeze performance of CASH gel is good, thereby improving the antifreeze performance of concrete. Therefore, low temperature has little effect on the initial setting time and final setting time of Examples 1-3. Compared with Comparative Example 3, the initial setting time and final setting time of Examples 1-3 are significantly shorter than those of Comparative Example 2, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH. The antifreeze performance of CASH gel is good, thereby improving the antifreeze performance of concrete. Therefore, low temperature has little effect on the initial setting time and final setting time of Examples 1-3. The initial setting time and final setting time of Examples 1-3 are equivalent to those of Comparative Example 3, indicating that the calcium hydroxide deactivator carboxylate-type corrosion inhibitor reduces the content of calcium hydroxide without affecting the initial setting time and final setting time of Examples 1-3; relative to Comparative Example 4, the initial setting time and final setting time of Examples 1-3 are significantly lower than those of Comparative Example 4, indicating that the hydrophilic polymer polyethylene oxide can reduce the free water in the cement paste, thereby reducing the fluidity and viscosity of the free water, promoting the hydration of C3S, and significantly shortening the initial setting time and final setting time of the concrete; relative to Comparative Example 5, the initial setting time and final setting time of Examples 1-3 are significantly lower than those of Comparative Example 4, indicating that the cationic surfactant carries a positive charge, reduces the viscosity of the cement paste, and reduces the initial setting time and final setting time of the concrete.
[0049] Experimental Example 2: Compressive Strength Test of Concrete Specimens After the silicate cement mortar samples of Example 1-3 and Comparative Examples 1-5 were set for 1 day and 28 days, the compressive strength of the concrete specimens was measured. The test method for the compressive strength of cement mortar was carried out according to the Chinese standard GB / T35159-2017 "Accelerator for Shotcrete". The compressive strength of the standard concrete specimens was tested using a compression testing machine. The cubic specimens were evaluated in groups of 3, and the arithmetic mean of the measured values of the three specimens was taken as the average compressive strength of the mortar cubic specimens of the group of specimens (accurate to 0.1MPa). When the difference between the maximum or minimum of the three measured values and the middle value exceeds 15% of the middle value, the maximum and minimum values are discarded together, and the middle value is taken as the compressive strength value of the group of specimens; if the difference between the two values and the middle value exceeds 15% of the middle value, the experimental results of the group of specimens are invalid. The results are shown in Table 2.
[0050] Compressive strength test: The compressive strength test is usually completed by placing the mortar specimen on a pressure testing machine and recording the maximum load before the specimen fails. The formula for calculating compressive strength is σ=P / S, where σ is the compressive strength of the specimen (in megapascals (MPa)), P is the failure load of the specimen (in Newtons (N)), and S is the compressive area of the specimen (in square millimeters (mm²)).
[0051] The 1-day compressive strength of mortar refers to the compressive strength of the mortar specimen measured after one day of curing under standard curing conditions. This indicator is of great significance for evaluating the early strength development and construction performance of mortar. Construction application: In actual construction, the 1-day compressive strength data can be used to evaluate whether the mortar is suitable for rapid construction or whether the curing time needs to be extended to ensure sufficient strength.
[0052] Table 2
[0053] The Chinese standard GB / T35159-2017 "Accelerators for Shotcrete" requires the 1-day compressive strength of mortar to be as follows: The 1-day compressive strength of mortar with alkali-free liquid accelerator is greater than or equal to 7MPa. The results in Table 2 show that the 1 d compressive strength and 28 d compressive strength of Examples 1-3 are significantly greater than those of Comparative Examples 2-5. Relative to Comparative Example 1, the 1 d compressive strength and 28 d compressive strength of Examples 1-3 are comparable to those of Comparative Example 1, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH, and the CASH gel has good antifreeze performance, thereby improving the antifreeze performance of concrete, and sodium thiocyanate has little effect on the strength of concrete; Relative to Comparative Example 2, the 1 d compressive strength and 28 d compressive strength of Examples 1-3 are significantly lower than those of Comparative Example 2, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH, and the CASH gel has good antifreeze performance, thereby improving the antifreeze performance of concrete; Relative to Comparative Example 3, the 1 d compressive strength and 28 d compressive strength of Examples 1-3 are significantly lower than those of Comparative Example 2, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH, and the CASH gel has good antifreeze performance, thereby improving the antifreeze performance of concrete. The 1 d compressive strength of Examples 1-3 is significantly higher than that of Comparative Example 3, indicating that the carboxylate-type corrosion inhibitor of calcium hydroxide deactivator reduces the content of calcium hydroxide, helps to refine the pore structure of concrete, increases the amount of gel and gel porosity, but reduces the capillary porosity, enhances the compactness of concrete, thereby reducing the transportation of water in concrete and improving the strength of concrete; relative to Comparative Example 4, the 1 d compressive strength of Examples 1-3 is equivalent to that of Comparative Example 4, but the 28 d compressive strength of Examples 1-3 is significantly higher than that of Comparative Example 4, indicating that the hydrophilic polymer polyethylene oxide can reduce the free water in the cement paste, thereby reducing the fluidity and viscosity of the free water, promoting the hydration of C3S, and significantly improving the later strength of the concrete; relative to Comparative Example 5, the 1 d compressive strength of Examples 1-3 is equivalent to that of Comparative Example 5, but the 28 d compressive strength of Examples 1-3 is significantly higher than that of Comparative Example 5, indicating that the cationic surfactant carries a positive charge, reduces the viscosity of the cement paste, and improves the later strength of the concrete.
[0054] Experimental Example 3: Antifreeze Performance Test After 28 days of curing, this experiment was conducted by pouring into a cylinder with a diameter of 10 cm and a height of 10 cm. According to GB / T50082-2019 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", a rapid freeze-thaw cycle test was conducted, and the mass loss of 5% was used as the basis for terminating the concrete frost resistance test. The test results are shown in Table 3.
[0055] Table 3
[0056] As can be seen from Table 3, the number of freeze-thaw cycles of Examples 1-3 is significantly greater than that of Comparative Example 2, indicating that polyaluminium chloride can achieve the doping of aluminium atoms in calcium silicate hydrate (CSH) gel to form CASH, and the CASH gel has good antifreeze performance, thereby improving the antifreeze performance of concrete; relative to Comparative Example 3, the number of freeze-thaw cycles of Examples 1-3 is significantly higher than that of Comparative Example 3, indicating that the calcium hydroxide deactivator carboxylate ester corrosion inhibitor reduces the content of calcium hydroxide, helps to refine the pore structure of concrete, increases the gel amount and gel porosity, but reduces the capillary porosity, enhances the compactness of concrete, and thus reduces the transport of water in concrete. , improve the strength of concrete, and help improve the frost resistance of concrete; relative to comparative example 4, the number of freeze-thaw cycles of Examples 1-3 is higher than that of Comparative Example 4, indicating that the hydrophilic polymer polyethylene oxide can reduce the free water in the cement paste, thereby reducing the fluidity and viscosity of the free water, promoting the hydration of C3S, significantly improving the later strength of the concrete, and helping to improve the frost resistance of the concrete; relative to comparative example 5, the number of freeze-thaw cycles of Examples 1-3 is higher than that of Comparative Example 5, indicating that the cationic surfactant carries a positive charge, reduces the viscosity of the cement paste, improves the later strength of the concrete, and helps to improve the frost resistance of the concrete.
[0057] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A low temperature resistant early strength alkali-free liquid accelerating agent, characterized in that: The invention comprises 12-15 parts of aluminum sulfate, 2-5 parts of sodium thiocyanate embedded in beta-cyclodextrin, 5-8 parts of calcium hydroxide deactivator, 3-5 parts of fiber, 5-10 parts of hydrophilic polymer substance, 3-5 parts of cationic surfactant, 6-10 parts of polyaluminum chloride and 2-3 parts of air entraining agent.
2. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The invention comprises 15 parts of aluminum sulfate, 2 parts of sodium thiocyanate embedded in beta-cyclodextrin, 8 parts of calcium hydroxide deactivator, 3 parts of fiber, 5 parts of hydrophilic polymer substance, 3 parts of cationic surfactant, 10 parts of polyaluminum chloride and 2 parts of air entraining agent.
3. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The calcium hydroxide deactivator is one or both of a carboxylate corrosion inhibitor and silica fume.
4. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The hydrophilic polymer substance is one or both of polyethylene oxide and polyacrylamide.
5. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The cationic surfactant is one or both of dodecyl dimethyl amine oxide and dodecylamine polyoxyethylene ether.
6. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The fiber is one or more of fiber steel fiber, glass fiber, basalt fiber, polypropylene fiber, nano carbon fiber, and polyacrylonitrile fiber.
7. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 3, characterized in that: The carboxylate corrosion inhibitor is a mixture of one or more of mono-aza-hybridized carboxylate, di-aza-hybridized di-carboxylate or fatty acid carboxylate.
8. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The air entraining agent is one or more of coconut oil fatty acid diethanolamide, sodium rosin acid, and triterpenoid saponin.
9. The low temperature resistant and early strength alkali-free liquid accelerating agent according to claim 1, characterized in that: The preparation method of the β-cyclodextrin-embedded sodium thiocyanate comprises the following steps: S1. Weigh β-cyclodextrin, add it into 70°C distilled water, stir and dissolve it, and adjust the pH value to 7.4 to obtain a β-cyclodextrin solution; S2. Weigh sodium thiocyanate and prepare a sodium thiocyanate ethanol solution in a mass ratio of 1:1, slowly add the sodium thiocyanate ethanol solution to the β-cyclodextrin solution, and stir at a constant temperature of 60° C. to 65° C. to promote the sodium thiocyanate molecules to enter the hydrophobic cavity of the β-cyclodextrin to form an inclusion complex, and then obtain the β-cyclodextrin-encapsulated sodium thiocyanate by suction filtration and drying.
10. The method for preparing a low temperature resistant and early strength alkali-free liquid accelerating setting agent according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh the raw materials of each component of the low-temperature resistant and early-strength alkali-free liquid accelerating setting agent according to the formula amount; S2, heating the deionized water to 70-85°C, then adding the aluminum sulfate, stirring until completely dissolved; cooling the solution to below 55°C, then adding the β-cyclodextrin-encapsulated sodium thiocyanate, the calcium hydroxide deactivator, the fiber, the hydrophilic polymer, the cationic surfactant, and the polyaluminum chloride, and stirring evenly; S3, adding the air entraining agent to the solution of step S2, stirring evenly, and cooling to room temperature to obtain the low-temperature stable and early-strengthening alkali-free liquid accelerating agent.
Citation Information
Patent Citations
High temperature resistance low-density high-strength cement paste
CN102585789A
Alkali-free high-strength concrete flash setting admixture
CN105753364A
Method for extracting sodium thiocyanate from ADA desulfurization waste liquid
CN108408740A
Anti-freezing alkali-free liquid accelerator and preparation method thereof
CN108516720A
Low rebound early strength liquid non-alkali setting accelerator and preparation method thereof
CN109180053A
Cited By
Fast-curing polyurethane grouting material for tunnel high-pressure water gushing plugging and preparation method of fast-curing polyurethane grouting material
CN122187450A